Gemology of Emeralds from Tauá, Brazil - Gomes de Oliveira, Isaac; de Sousa Carneiro, Laryssa; de Oliveira Cunha, Alina; Fernandes Alves, Conceição Regina; Czar dos Santos, Gabriel; Groat, Lee Andrew; dos Santos, Lucilene; de Araújo Paschoal, Carlos William; de Oliveira Neri, Tereza Falcão (Anuário do Instituto de Geociências, 2025)
In Brazilian territory many occurrences do not have their gemological and optical properties documented or made public. This research aimed to analyze the mineralogical and gemological aspects of emeralds from the city of Tauá (Brazil), utilizing gemological instruments such as a refractometer, dichroscope, spectroscope, polariscope, hydrostatic balance, ultraviolet lamp, and gemological microscope. The examined emeralds exhibit typical features found in emeralds worldwide, except for an above-average birefringence, similar to certain beryls from the state of Ceará. This highlights the significance of gemological characterization not only at the regional levels but also on a localized scale. Additionally, studying occurrences in varied geological settings is essential, as the formation environment influences mineral properties.